1996
DOI: 10.1093/hsw/21.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Gay Men with AIDS and Their Families of Origin: An Analysis of Social Support

Abstract: This article reviews the literature on the relationships between gay men with AIDS and their families of origin to determine why the family is not a principal source of social support. Several reasons explain the absence of the family from the support network, including the family's lack of acceptance of homosexuality and the relationship with a male partner; the stigma associated with AIDS; the inability of family members to communicate openly about homosexuality and AIDS; the lack of competence among family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 0 publications
2
35
0
1
Order By: Relevance
“…The most devastating consequences were with breakups or major stressors on sexual relations as experienced by about 17% of the participants, and the loss of relationships with family members in an additional 16% of cases. Our results are consistent with prior studies focusing on patients with HIV/AIDS or tuberculosis, who also felt rejected by relatives and friends [24,25] . While all chronic diseases can potentially tax a social support network, a diagnosis with HCV appeared to carry with it unique challenges.…”
Section: Discussionsupporting
confidence: 93%
“…The most devastating consequences were with breakups or major stressors on sexual relations as experienced by about 17% of the participants, and the loss of relationships with family members in an additional 16% of cases. Our results are consistent with prior studies focusing on patients with HIV/AIDS or tuberculosis, who also felt rejected by relatives and friends [24,25] . While all chronic diseases can potentially tax a social support network, a diagnosis with HCV appeared to carry with it unique challenges.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were found in studies of patients with HIV/AIDS and tuberculosis, where patients expressed the feeling of being shunned by those to whom they felt closest. 36,37 Such experiences result in adverse effects on well-being, as expressed by many of the patients interviewed here or as reported in the literature. 38 While hepatitis C plays an important role in triggering fears and concerns, psychosocial problems may, in some individuals, result from preexisting personality traits that can lead to risk-taking behavior and which may have resulted in the acquisition of hepatitis C. 39 However, the likelihood of experiencing stigmatization did not correlate with differences in the mode of acquisition, indicating that emotional problems cannot be simply explained by drug abuse and the associated personality and psychosocial problems.…”
Section: 29mentioning
confidence: 67%
“…Minority women with AIDS have many other life stressors including single parenthood (Marcenko & Samost, 1999), unstable income and limited access to health care (Gonzalez-Calvo, Jackson, Hansford, & Woodman, 1998). Of particular relevance to the objectives of this study, depression has been found to be related to disease progression and mortality in women with HIV (Ickovics et al, 2001 Numerous studies have documented the prevalence of distress among HIV/AIDS infected individuals (Chandra, Ravi, Desai, & Subbakrishna, 2001;Fukunishi et al, 1997) and have linked this distress to stressful life events (Crystal & Kersting, 1998), health status (Grassi et al, 1999), illness-related stressors, including social stigmatization (Kadushin, 1996) and cognitive deficits (Claypoole et al, 1998), loss of employment and autonomy (Hoffman, 1991) and faster disease progression (Cruess et al, 2003;Leserman, 2003).…”
Section: Aids; Cbsm+; Depression; Womenmentioning
confidence: 96%
“…Minority women with AIDS have many other life stressors including single parenthood (Marcenko & Samost, 1999), unstable income and limited access to health care (Gonzalez-Calvo, Jackson, Hansford, & Woodman, 1998). Of particular relevance to the objectives of this study, depression has been found to be related to disease progression and mortality in women with HIV (Ickovics et al, 2001 Numerous studies have documented the prevalence of distress among HIV/AIDS infected individuals (Chandra, Ravi, Desai, & Subbakrishna, 2001;Fukunishi et al, 1997) and have linked this distress to stressful life events (Crystal & Kersting, 1998), health status (Grassi et al, 1999), illness-related stressors, including social stigmatization (Kadushin, 1996) and cognitive deficits (Claypoole et al, 1998), loss of employment and autonomy (Hoffman, 1991) and faster disease progression (Cruess et al, 2003;Leserman, 2003).Cognitive-behavioral interventions have been found to be successful in reducing distress associated with human immunodeficiency virus (HIV) disease (Church, 1998;Kelly et al, 1993). Investigators from our research team have tested the utility of a targeted cognitivebehavioral stress management (CBSM) intervention in reducing distress in gay men with clinically significant results (Antoni et al, 1991;Lutgendorf et al, 1997), as well as predicting clinical outcomes (Ironson et al, 1994) for those with better attendance.…”
mentioning
confidence: 96%